Tackling COVID-19 (European Stadium & Safety Management Association, 2020)
COVID-19 has substantially disrupted all stadium-related business. This has had a huge impact on all our members. However, as ESSMA is a member association, we aim to keep you informed on stadium-related business, with a dedicated focus on how clubs and stadiums are handling the current challenges and the impact on the future matchday operations.